Simulation Study of an ORC System Driven by the Waste Heat Recovered from a Trigeneration System. (May 2017) - Ji, Jie; He, Cui; Xiao, Zheng; Miao, Chunqiong; Luo, Liqi; Chen, Haisheng; Zhang, Xinjing; Guo, Huan; Wang, Yaodong; Roskilly, Tony
Abstract: Trigeneration produces power, heat and cooling simultaneously. It utilises the waste heat from generator for heating and generating cooling. From previous studies, it is found that some part of the waste heat recovered by the trigeneration is not being used when it is in operation. It is therefore necessary to find a way to utilise the heat. Integrating an ORC (organic Rankine cycle) system into a micro trigeneration system is studied. The waste heat recovered by the trigeneration system is utilised by the ORC system to generate electrical power. An ORC model is set up in Matlab and a micro trigeneration system based a diesel engine generator in the laboratory at Newcastle University is used as the case study. R245fa is used as the working fluid. The result showed that the ORC system may generate 0.737 kW electrical power with 9.25% efficiency at the generator full-load operation point.